Osteoid osteoma in a metacarpal bone: literature review and case report - Mendoza Vélez, Maria de los Angeles; Rendon Medina, Marco Aurelio; Viana, Erik Hanson; Rojas Ortiz, Jorge Arturo; Lopez, Ricardo Pacheco (International Journal of Research in Medical Sciences, 2022)
Osteoid osteomas are benign skeletal tumors; more than half of the lesions occur in lower extremity long bones, with very few cases reported in metacarpal bones. We presented the case of a patient at the plastic surgery department of a regional hospital, who presented with a tender tumor in the left hand over the past 2 years.